Pleural mass in a young male unfolding an uncommon presentation of multiple myeloma (Journal of Pathology of Nepal, 2020)
Multiple myeloma is a malignant proliferation of the plasma cells and can be non-secretory in about 1 to 5 % cases. Pleura based mass lesions are uncommon in myeloma. Herein we report a case of non-secretory multiple myeloma presenting with a pleura based mass in a 40 year old male. Fine needle aspiration cytology with immunohistochemistry played a key role in the diagnosis of this case.